An online questionnaire survey of UK general practitioners' knowledge and management of familial hypercholesterolaemia. Issue 11 (9th November 2016) - Kwok, See; Pang, Jing; Adam, Safwaan; Watts, Gerald F; Soran, Handrean
Abstract : Objective: Early diagnosis and treatment of heterozygous familial hypercholesterolaemia (HeFH) is known to be associated with reduced mortality from premature coronary artery disease, but HeFH remains underdiagnosed. This survey aims to determine knowledge and current management of HeFH in general practice. Setting: An online questionnaire was administered to general practitioners' (GPs') in the North West of England to assess their knowledge and management of HeFH. Participants: Practising GPs in the North West of England were contacted by email and invited to complete an online questionnaire. Recruitment discontinued when the target of 100 was reached. Primary outcome: An assessment of the knowledge and current management of HeFH in GPs. Results: 100 GP responses were analysed. Although only 39% considered themselves to have reasonable knowledge of HeFH, 89% knew that HeFH was a genetic disorder and 74% selected the correct lipid profile for diagnosing the condition. More than half (61%) were aware of current guidelines on HeFH. Gaps in knowledge were evident when only 30% correctly identified the prevalence of HeFH and half were not aware of the pattern of inheritance. Increased cardiovascular risk was underestimated by majority. 33% thought that they had HeFH patients in their practice confirming underdiagnosis of the condition. Statin therapy was recognised by 94% to be the right medication for treating HeFH. The majority (82%) regarded GPs to be the most effective healthcare professional for early recognition of HeFH. Conclusions: GPs have an above-average knowledge of familial hypercholesterolaemia (FH) and almost universally consider that they have a key role in the early recognition of undiagnosed HeFH patients in the community. However, there are gaps in awareness that need to be addressed to further enhance the care of FH in the community.